PENGARUH GAYA KEPEMIMPINAN SITUASIONAL, KARAKTERISTIK INDIVIDU, MOTIVASI, DAN DISIPLIN TERHADAP KINERJA ORGANISASI BISNIS - Harsapranata, Agni Isador (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2016)
This research aims to determine the effect of situational leadership, individual characteristics, motivation, and discipline on the performance of business organizations in Astrido Group. This research was conducted in the office Astrido Group Jakarta.The method used in this research is to conduct a survey, with a sample of 264 people. Data analysis was performed by multiple regression analysis between independents variables (situational leadership, individual characteristics, motivation, and discipline) and the dependent variable (performance business organizations). From the analysis and hypothesis testing, is known to have a positive and significant effect simultaneously between variables competency, compensation to employee performance, and a positive and significant effect partially between competence and compensation variables. Based on these results, it was concluded that the performance of employees Astrido Group will be increased by increasing the competency, and compensation. Keywords : situational leadership, individual characteristics, motivation, discipline